2020
DOI: 10.21511/bbs.15(4).2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Sharia corporate governance and financial reporting timeliness: Evidence of the implementation of banking regulations in Indonesia

Abstract: This paper aims to study Islamic banking (IB) regulations related to the influence of the Sharia corporate governance (SCG) mechanism on financial reporting timeliness (FRTL) in Indonesia. The unbalanced panel data obtained empirically during a period that ranges from 2016 to 2019 includes observations from 54 Islamic commercial banks (ICb), 82 Sharia business unit (SBu) banks and 82 conventional banks (CB). Panel regression model is used in this study to adjust the unbalanced panel data obtained. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…Given their critical role in the operation of the Islamic banking sector, the composition of influential Shariah committees is another factor that might impact Islamic banking institutions' business-related risks and audit report lag. Rusmin and Evans (2017), Oussii and Boulila Taktak (2018), Kaaroud et al (2020) and Zulfikar et al (2020) found a negative association between Shariah committee expertise and audit report lag. Having accounting/financial knowledge within the Shariah committee may aid the committee in dealing with Shariah concerns, particularly those involving accounting/financial matters.…”
Section: Shariah Committee Expertisementioning
confidence: 95%
See 3 more Smart Citations
“…Given their critical role in the operation of the Islamic banking sector, the composition of influential Shariah committees is another factor that might impact Islamic banking institutions' business-related risks and audit report lag. Rusmin and Evans (2017), Oussii and Boulila Taktak (2018), Kaaroud et al (2020) and Zulfikar et al (2020) found a negative association between Shariah committee expertise and audit report lag. Having accounting/financial knowledge within the Shariah committee may aid the committee in dealing with Shariah concerns, particularly those involving accounting/financial matters.…”
Section: Shariah Committee Expertisementioning
confidence: 95%
“…In addition, the committee should be informed of the banks' operational risks and financial performance, as they are essential factors in developing a thriving financial product. Zulfikar, Bawono, Mujiyati, and Wahyuni (2020) and Kaaroud et al (2020) have studied the association between the Shariah board characteristics and audit report delay. In a study in Indonesia, Zulfikar et al (2020) concluded that the presence of a Shariah committee could reduce audit report delays.…”
Section: Shariah Committee Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this empirical study indicate that SSB members with accounting and/or finance specialists (H2a) cannot moderate the detrimental impact of CEO hubris on IBs' performance. Their membership can be considered only related to the process and analysis of financial reporting(Baklouti, 2020;Khan & Zahid, 2020;Zulfikar et al, 2020), regardless of the CEO behavior. However, this study succeeded in proving that the vigilance of reputable SSB members weakened the bad influence of CEO hubris on IBs' performance (H2b).…”
mentioning
confidence: 99%